Antiproliferative activity and p53 upregulation effects of chalcones on human breast cancer cells - dos Santos, Mariana Bastos [UNESP]; Bertholin Anselmo, Daiane [UNESP]; de Oliveira, Jéssica Gisleine; Jardim-Perassi, Bruna V.; Alves Monteiro, Diego [UNESP]; Silva, Gabriel; Gomes, Eleni [UNESP]; Lucia Fachin, Ana; Marins, Mozart; de Campos Zuccari, Débora Aparecida Pires; Octavio Regasini, Luis [UNESP] (Taylor & Francis, 2019)
Chalcones are valuable structures for drug discovery due to their broad bioactivity spectrum. In this study, we evaluated 20 synthetic chalcones against estrogen-receptor-positive breast cancer cells (MCF-7 line) and triple-negative breast cancer (TNBC) cells (MDA-MB-231 line). Antiproliferative screening by MTT assay resulted in two most active compounds: 2-fluoro-4’-aminochalcone (11) and 3-pyridyl-4’-aminochalcone (17). Their IC50 values ranged from 13.2 to 34.7 µM against both cell lines. Selected chalcones are weak basic compounds and maintained their antiproliferative activity under acidosis conditions (pH 6.7), indicating their resistance to ion-trapping effect. The mode of breast cancer cells death was investigated and chalcones 11 and 17 were able to induce apoptosis rather than necrosis in both lines. Antiproliferative target investigations with MCF-7 cells suggested 11 and 17 upregulated p53 protein expression and did not affect Sp1 protein expression. Future studies on chalcones 11 and 17 can define their in vivo therapeutic potential.
Keywords: antiproliferative; apoptosis; cancer; Chalcones; p53